2001
DOI: 10.1111/0021-8294.00086
|View full text |Cite
|
Sign up to set email alerts
|

Work, Family, and Religious Involvement for Men and Women

Abstract: Do family formation and social establishment affect religious involvement in the same way for men and women, given increasing individualism and rapid changes in work and family roles? Using a random sample of adults from upstate New York (N = 1,006), our research builds on previous work in this area by using multiple measures of religious involvement, using multiple measures of individualism and beliefs about work and family roles, placing men and women in their work context, and looking at the relationships s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 28 publications
1
53
0
1
Order By: Relevance
“…Daniels, 1988, pp. 4-6;Becker & Hofmeister, 2001). Even though females are far less likely to be clergy, ordained or not, than males (Zikmund et al, 1998, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Daniels, 1988, pp. 4-6;Becker & Hofmeister, 2001). Even though females are far less likely to be clergy, ordained or not, than males (Zikmund et al, 1998, pp.…”
Section: Introductionmentioning
confidence: 99%
“…From one perspective, the study of religious personal identity has largely been limited to studies outside the work context, such as examinations of religious involvement (Becker & Hofmeister, 2001) or death attitudes (Ladd, 2007), to name a few (for an exception, see Moore, 2008). This study contributes to the literature by also demonstrating that one's religious personal identity contributes to her or his perceptions of the self relative to others.…”
Section: Discussionmentioning
confidence: 93%
“…Note that in both cases, people who hold a particular set of religious beliefs; it is the strength of those beliefs and how central they are to one's perception of the self that differ. Such variability highlights the importance one's religious personal identity, or the level of importance placed on one's religion (for related work, see Becker & Hofmeister, 2001;Ladd, 2007;Markus, 1977). As Brewer (1991) notes, one's personal identity is an identity an individual holds that is perceived as critical to his or her self-concept.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Because Jewish women are at the forefront of such changes in labor force participation and occupational achievement, it would be expected that any such changes would certainly show up among Jews. However, Becker and Hofmeister (2001), in their research using a national sample of around 1,000, found that not only is women's religious involvement lower when they are employed full time, but so is their spouse's, suggesting that something else is going on. Becker and Hofmeister discuss the possibility that women's employment is accompanied by a greater individualism and a decreased willingness to assume the traditionally gendered roles that are historically associated with religious institutions, echoing some of the suggestions made by Walter and Davie (1998).…”
Section: Gender Differences In Religious and Ethnic Identitymentioning
confidence: 98%